Autologous osteoperiosteal transplantation achieves comparable repair effect and superior interface integration to autologous osteochondral transplantation in porcine osteochondral defects - Shuai Yang; En Deng; Linxin Chen; Yanbin Pi; Anhong Wang; Linghui Dai; Hongjie Huang; Xiaoning Duan; Xin Fu; Jiying Zhang; Qinwei Guo; Weili Shi (Journal of Orthopaedic Translation)
Background: Autologous osteochondral transplantation (AOCT) has been established as an effective treatment strategy for osteochondral defects. Additionally, autologous osteoperiosteal transplantation (AOPT) has emerged as a promising alternative with comparable clinical efficacy. However, a notable gap in the literature exists regarding the specific repair process by the periosteal graft. Therefore, the primary objective of the present study was to assess the osteochondral repair efficacy of AOPT using a porcine model and to elucidate the repair process of the periosteal graft. Hypothesis: AOPT would achieve similar repair effect to AOCT and the grafted periosteum would progressively transform into cartilage-like tissue. Methods: Cylindrical osteochondral defects (8.0 mm in diameter and 5.0 mm in depth) were surgically created bilaterally at the center of the medial femoral condyles in 27 Guangxi Bama minipigs. The 54 knees were randomly allocated into three groups: negative control (n = 18), AOCT (n = 18), and AOPT (n = 18). Osteochondral grafts were harvested from non-weightbearing area of the femoral notch, while osteoperiosteal grafts were from the ipsilateral iliac crest. At 2, 4, and 6 months post-surgery, the knees were subjected to macroscopic, radiographic, nanoindentation and histological evaluations. Results: At 2, 4, and 6 months postoperatively, the gross view evaluation using the International Cartilage Repair Society (ICRS) scoring system and the imaging assessment with the magnetic resonance observation of cartilage repair tissue (MOCART) scoring system showed similar results in the AOCT and AOPT groups, both superior to those of the control group. Nanoindentation analysis revealed near-normal biomechanical properties in the repaired cartilage of both AOPT and AOCT groups. Histological evaluation indicated that the quality of repaired tissues in the AOPT group was comparable to that in the AOCT group. Notably, AOPT consistently exhibited superior interface integration compared to AOCT at all time points. Conclusion: Both AOPT and AOCT demonstrate significant efficacy in promoting the repair of osteochondral defects in a porcine model. Despite similar radiographic findings, mechanical performance and histological structure displayed in both grafted groups, AOPT exhibit superior interface integration, which is critical for effective tissue restoration. The translational potential of this article: As a recently developed procedure for treating osteochondral defects, AOPT has shown promising repair effect and is being increasingly adopted in clinical practice. This study presents histological evidence of the progressive transformation of the periosteum graft into cartilage-like tissue and demonstrates its ability to integrate with the surrounding tissue.